The use of non-standard Malaysian English among students in a Chinese vernacular school / Lee Mong Lui - Lee, Mong Lui (2015)
English is the second language in Malaysia and it is used by different ethnic communities. This situation could have contributed to the unique characteristics of Malaysian English (ME). ME can be distinguished in two categories- the Standard Malaysian English (SME) and the Non-Standard Malaysian English (Manglish). This study focuses on Manglish which is used among Chinese vernacular school students. The research aims to examine the lexical and syntactic features of Manglish. It also aims to identify the choice and usage of Manglish an SME in formal and informal situations. To achieve these aims, a combination of research methods and procedures were employed. Qualitative and quantitative methods are used to analyze the data which are collected through a listening activity, questionnaires and oral interaction recordings. Some of the main findings of this research indicated that Mandarin- medium vernacular school students: 1. Use various particles (lah, mah, ah) frequently; 2. Omit the subject in the noun phrase structure; 3. Use Manglish with friends in informal situations and also during lessons (English lessons and Mathematics and Science in English lessons); 4. Usually use SME with teachers in formal situations. This study also provides recommendations to address the issue of Manglish usage in schools. It is hoped that the study can be used as a guide in researching the usage of Manglish in schools in general and the effects of Manglish usage in particular.